Lichens of the Frankenhalvøya Peninsula, Northern of Barentsøya, Svalbard - Konoreva, Liudmila; Chesnokov, Sergey (Polish Polar Research, 2021)
This paper contributes to the studies on the lichen diversity of Barentsøya. It covers 211 species, of which four (Buellia schaereri, Myriolecis zosterae var. palanderi, Rhizocarpon furfurosum, R. leptolepis) are reported for the first time for the Svalbard archipelago. Additionally, 84 of the species are reported for the first time for Barentsøya. Our study includes 2 subspecies as well, both new for Barentsøya. Thirty-six species (16.8% among the identified species) are rare in Svalbard, whereas more than two thirds (70.1% from identified in the Barentsøya) are relatively widespread species in Svalbard and the Arctic.